1980
DOI: 10.1007/bf00892282
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals' perceptions of the psychological consequences of abortion

Abstract: Measures of depression, guilt, and state and trait anxiety were administered to doctors, nurses, and social workers under two conditions, self-report and role play. In the role-play condition, they were asked to complete the questions as would a woman who had undergone an abortion the previous day. Half of the subjects in each group were experienced with abortion patients, and half were inexperienced students. All three professional groups expected extreme depression, guilt, and anxiety on the part of the abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Fourteen articles categorized under nurses’ attitudes and perceptions toward abortion care or 24% were consistent with this heading (Baluk & O'Neill, ; Fischer, ; Gallagher, Porock, & Edgley, ; Hudson‐Rosen, Werley, Ager, & Shea, ; Kaltreider, Goldsmith, & Margolis, ; Likis, ; Lipp, ; Marek, ; Marshall, Gould, & Roberts, ; McKee & Adams, ; Neustatter, ; Sandroff, ; Swenson, Swanson, & Oakley, ; Webb, ). The articles grouped under this theme include attitudes of staff nurses (Hendershot & Grimm, ; Kaltreider et al; Marek; Marshall et al; Neustatter; Sandroff; Swenson et al; Webb), nurse‐midwives (Glenn, ; Likis; Lipp; McKee & Adams), and other health care professionals with nurses included (Baluk; Fischer; Hudson‐Rosen et al).…”
Section: Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen articles categorized under nurses’ attitudes and perceptions toward abortion care or 24% were consistent with this heading (Baluk & O'Neill, ; Fischer, ; Gallagher, Porock, & Edgley, ; Hudson‐Rosen, Werley, Ager, & Shea, ; Kaltreider, Goldsmith, & Margolis, ; Likis, ; Lipp, ; Marek, ; Marshall, Gould, & Roberts, ; McKee & Adams, ; Neustatter, ; Sandroff, ; Swenson, Swanson, & Oakley, ; Webb, ). The articles grouped under this theme include attitudes of staff nurses (Hendershot & Grimm, ; Kaltreider et al; Marek; Marshall et al; Neustatter; Sandroff; Swenson et al; Webb), nurse‐midwives (Glenn, ; Likis; Lipp; McKee & Adams), and other health care professionals with nurses included (Baluk; Fischer; Hudson‐Rosen et al).…”
Section: Themesmentioning
confidence: 99%
“…Fourteen articles categorized under nurses' attitudes and perceptions toward abortion care or 24% were consistent with this heading (Baluk & O'Neill, 1980;Fischer, 1979;Gallagher, Porock, & Edgley, 2010;Hudson-Rosen, Werley, Ager, & Shea, 1974;Kaltreider, Goldsmith, & Margolis, 1979;Likis, 2009;Lipp, 2008;Marek, 2004;Marshall, Gould, & Roberts, 1994;McKee & Adams, 1994;Neustatter, 1980;Sandroff, 1980;Swenson, Swanson, & Oakley, 1994;Webb, 1985). The articles grouped under this theme include…”
Section: Nurses' Attitudes and Perceptions Toward Abortion Carementioning
confidence: 99%
“…Recent public debate about abortion implies the presence of a post-abortion syndrome, consisting of "a sense of loss, of emptiness, of grief" (Suwiving Abortion: Help for the Aboned Woman, 1986, p. 4). Baluk and O'Neill (1980) found that health professionals who worked with abortion patients predicted anxiety, depression and guilt, none of which matched the self-reports of the women. This paper reviews the literature regarding the emotions women experience after abortion.…”
mentioning
confidence: 85%
“…In studies comparing nurses with other professionals (Baluk & O'Neill, 1980;Darity & Thibaux, 1969;Hertel et al, 1974;Leif & Payne, 1975;Werley et al, 1973), nurses were less supportive of family planning, but the differences may have been due to the different composition of the nurse and other sample groups. For instance, Werley and Ager (1975) found that nurses had less favorable attitudes about family planning than did physicians and social workers, but these differences were largely accounted for by religion, frequency of church attendance, and race.…”
mentioning
confidence: 94%